FACTORS ASSOCIATED WITH TYPE 2 DIABETES MELLITUS AMONG THE ELDERLY IN CINERE SUBDISTRICT, DEPOK - Nadhira Zarfani Ilham (2023)
Background: Basic health research (Riskesdas) stated that the prevalence of type 2 diabetes mellitus (T2DM) nationwide has increased. Due to deficiency of insulin secretion and increased insulin resistance with age, the elderly population is more susceptible to T2DM. Various factors, changeable and unchangeable, contribute to the incidence of T2DM; sex, nutritional status, level of education, occupational history, smoking history, and diabetes family history among them. This study was conducted to determine the factors associated with T2DM in Cinere subdistrict, Depok. Method: Cross-sectional design with a stratified random sampling technique was used, and involved 108 participants. Data was collected by filling out a questionnaire and processed using the chi-square test. Results: There is no relationship between sex (P = 0.865), level of education (P = 0.891), smoking and T2DM (P = 0.525). There is a relationship between nutritional status (P = 0.016), occupational history (P = 0.036), diabetes family history (P = 0.021) and T2DM. Conclusion: nutritional status, occupational history, and diabetes family history are associated with T2DM. Suggestion: Maintaining a healthy lifestyle during productive age is needed to prevent the incidence of NCDs, including T2DM, in the later years of life.